STRATEGI MENINGKATKAN KINERJA ORGANISASI MELALUI INOVASI TRANSFORMASI BUDAYA PROSOSIAL - Endang Tjahjaningsih (Jurnal Bisnis dan Ekonomi, 2013)
The purpose of this study to develop a theoretical approach to track and analyze the development to Innovation of Prosocial Cultural Transformation improve organizational  performance. This research is expected to provide an explanation to fill this research gap related to the presence of entrepreneurs in the batik industry is the thing that can not be circumvented in wanting to improve the performance of the organization's success in a competitive business environment associated with the implementation of the innovation strategy. The research was conducted in the area of Pekalongan, Rembang, Sragen, Solo, dan Banjarnegara Central Java Province. The sample size of the study was 200 owners/ leaders/ managers of Small and Medium Scale Enterprises. The variables of innovation of prosocial cultural transformation measured through creative product development, creative technique based on cost efficiency, and responsibility to employees and the community to achieve improved organizational performance. The result showed that consumer orientation, supplier orientation, employee creativity affect positively towards innovation of prosocial cultural transformation. Afterwards, innovation of prosocial cultural transformation affect positively towards organizational performance. This research was based on Resources Based Theory and Diversity in Innovation Theory which means that the company's success is based on the characteristics of the resources in the company.The limitation and implication for the future study and the managerial implication are alsodiscussed in this study. Key words: consumer orientation, supplier orientation, employee creativity, innovation of prosocial cultural transformation, organizational performance.